Family Resilience in the Oncology Setting: Development of an Integrative Framework - Faccio, Flavia; Renzi, Chiara; Giudice, Alice V.; Pravettoni, Gabriella (Frontiers in Psychology, 2018)
Resilience is a concept that has received burgeoning interest in the last decades. Researchers have been fascinated by the ability of some individuals to bounce back from an adverse event and adapt to extremely challenging situations. More recently family resilience, namely the potential resources of the family’s system, has been considered due to numerous individual studies highlighting the crucial influence of relationships with significant others in mediating adaptation and recovery. In this article, a brief overview of the theoretical literature on individual and family resilience is presented. Following, current empirical literature on resilience in the context of oncology is evaluated. Although family resilience is considered a dynamic process unique to each family unit, some common resources and strengths that can help families face significant adversities, such as cancer, can be identified. This said to date there is no family resilience framework applied specifically to the cancer trajectory. Drawing from previous studies, we sought to provide a clinical resilience model for families living with cancer, with the aim of mapping those resources that can empower families to deal with prolonged adversity. This framework can serve as general guideline for health professionals in assessing family strengths, promoting specific family processes and facilitating adaptation to the cancer experience.